The late endosomal p14–MP1 (LAMTOR2/3) complex regulates focal adhesion dynamics during cell migration - Schiefermeier, Natalia (The Rockefeller University Press, 2014)
Cell migration is mediated by the dynamic remodeling of focal adhesions (FAs). Recently, an important role of endosomal signaling in regulation of cell migration was recognized. Here, we show an essential function for late endosomes carrying the p14–MP1 (LAMTOR2/3) complex in FA dynamics. p14–MP1-positive endosomes move to the cell periphery along microtubules (MTs) in a kinesin1- and Arl8b-dependent manner. There they specifically target FAs to regulate FA turnover, which is required for cell migration. Using genetically modified fibroblasts from p14-deficient mice and Arl8b-depleted cells, we demonstrate that MT plus end–directed traffic of p14–MP1-positive endosomes triggered IQGAP1 disassociation from FAs. The release of IQGAP was required for FA dynamics. Taken together, our results suggest that late endosomes contribute to the regulation of cell migration by transporting the p14–MP1 scaffold complex to the vicinity of FAs.